2018
DOI: 10.1186/s13690-018-0318-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of human biomonitoring in the Dehcho region of the Northwest Territories, Canada (2016–2017)

Abstract: BackgroundHuman biomonitoring represents an important tool for health risk assessment, supporting the characterization of contaminant exposure and nutrient status. In communities where country foods (locally harvested foods: land animals, fish, birds, plants) are integrated in the daily diet, as is the case in remote northern regions where food security is a challenge, such foods can potentially be a significant route of contaminant exposure. To assess this issue, a biomonitoring project was implemented among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Random selection recruitment was combined with word of mouth and poster recruitment, aiming to represent the gender and age distribution of the local population. The larger project, funded by the Northern Contaminants Program, involved the collection of three biological samples (human hair, urine and blood), the administration of two dietary surveys (the FFQ and a 24-h dietary recall) and a Health Messages Survey to characterise knowledge awareness, risk perception and communication preferences (10) . Participants had the choice to take part in any number of the six components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random selection recruitment was combined with word of mouth and poster recruitment, aiming to represent the gender and age distribution of the local population. The larger project, funded by the Northern Contaminants Program, involved the collection of three biological samples (human hair, urine and blood), the administration of two dietary surveys (the FFQ and a 24-h dietary recall) and a Health Messages Survey to characterise knowledge awareness, risk perception and communication preferences (10) . Participants had the choice to take part in any number of the six components.…”
Section: Methodsmentioning
confidence: 99%
“…The findings of the CINE project indicated that game birds make up an important part of the country foods consumed for First Nations, Inuit and Métis in Canada. Our community-based human biomonitoring project was more recently implemented in the NWT in 2015-2018, with the aim of investigating contaminant exposures, nutrition markers and the role of country foods (9,10) . Of the ten most consumed country foods in the larger study, two were birds (Canada goose and mallard) (11) , highlighting the importance of waterfowl for food security and nutrition, and a need to more closely examine bird consumption.…”
mentioning
confidence: 99%
“…A total of 537 participants in the NWT consented to participate in the project. This project, funded by the Northern Contaminants Program (NCP), involved the collection of three biological samples (human hair, urine, and blood), the administration of two dietary surveys (an FFQ and a 24-h dietary recall) and a Health Messages Survey to characterise knowledge awareness, risk perception, and communication preferences [16]. Participants had the choice to take part in any number of the six components.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of participant recruitment for the project can be found in Ratelle et al [16]. Recruitment was done during the winter season (November to March) and efforts were aimed for participants to represent the sex and age distribution of the combined population (i.e., children, young adults, Elders).…”
Section: Implementing the Ffq In The Mackenzie Valley Biomonitoring Pmentioning
confidence: 99%
See 1 more Smart Citation